Music therapy: Storytelling with the special needs children - Abd Rahim, Normaliza; Zainon Hamzah, Zaitul Azma; Sujud, Arba'ie (The International Journal of Interdisciplinary Social Sciences, 2008)
This research investigates the effect of music therapy towards storytelling with special needs children. Music therapy is the structured use of music experiences to facilitate positive changes in human behaviour. It is a professional discipline that uses music to achieve therapeutic aims (Daveson & Edwards, 1998). Music therapy in special education is the functional use of music to achieve and enhance special education goals, while offering an alternative to traditional teaching methods (Daveson & Edwards, 1998). Positive changes in human behaviour means that music therapy aims to help special needs children to develop skills that have to do with overall development and personal growth. Children involved in this study are autistics. Autism is a complex developmental disability that typically appears during the first three years of life. Autism impacts the normal development of the brain in the areas of social interaction and communication skills (Dawson, G., Toth, K., Abbott, R., Osterling, J., Munson, J., Estes, A., and Liaw, J., 2004). Children with autism typically have difficulties in verbal and non-verbal communication, social interactions, and leisure or play activities. The disorder makes it hard for them to communicate with others and relate to the outside world. Therefore, this study is to use music therapy to enhance the subjects to concerntrate on the story told by the teacher and also able to storytell to the class. Subjects consist of 4 autistic children from Melaka, Malaysia ages between 8 to 12 years old. It is found that autistic children able to understand the story and to storytell to the rest of the classroom. Music therapy had made the autistic children feel happy and always in a calm situation.